A pilot study to assess the practicality, acceptability and feasibility of a randomised controlled trial to evaluate the impact of a pharmacist complex intervention on patients with stroke in their own homes. Issue 2 (8th August 2016) - Souter, Caroline; Kinnear, Anne; Kinnear, Moira; Mead, Gillian
Abstract : Objective: To test the practicality, acceptability and feasibility of recruitment, data collection, blood pressure (BP) monitoring and pharmaceutical care processes, in order to inform the design of a definitive randomised controlled trial of a pharmacist complex intervention on patients with stroke in their own homes. Methods: Patients with new stroke from acute, rehabilitation wards and a neurovascular clinic (NVC) were randomised to usual care or to an intervention group who received a home visit at 1, 3 and 6 months from a clinical pharmacist. Pharmaceutical care comprised medication review, medicines and lifestyle advice, pharmaceutical care issue (PCI) resolution and supply of individualised patient information. A pharmaceutical care plan was sent to the General Practitioner and Community Pharmacy. BP and lipids were measured for both groups at baseline and at 6 months. Questionnaires covering satisfaction, quality of life and medicine adherence were administered at 6 months. Results: Of the 430 potentially eligible patients, 30 inpatients and 10 NVC outpatients were recruited. Only 33/364 NVC outpatients (9.1%) had new stroke. 35 patients completed the study (intervention=18, usual care=17). Questionnaire completion rates were 91.4% and 84.4%, respectively. BP and lipid measurement processes were unreliable. From 104 identified PCIs, 19/23 recommendations (83%) made to general practitioners were accepted. Conclusion: Modifications to recruitment is required to include patients with transient ischaemic attack. Questionnaire response rates met criteria but completion rates did not, which merits further analysis. Lipid measurements are not necessary as an outcome measure. A reliable BP-monitoring process is required.